2011
DOI: 10.1111/j.1468-1331.2010.03135.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular dysautonomia in de novo Parkinson’s disease without orthostatic hypotension

Abstract: These results show that latent cardiac and vasomotor sympathetic dysfunction but not parasympathetic dysfunction is already present in early stage de novo PD, even without orthostatic hypotension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
36
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 65 publications
5
36
0
Order By: Relevance
“…In both groups, LF (ms 2 ) values were considerably increased in magnitude but different from each other during CB, a condition known to augment cardiovagal control 21 . Nevertheless this finding does not reflect sympathetic dominance but rather an effect of low respiratory frequency (,0.2 Hz), which causes an overlap of the LF and HF components of CVV signals 22,26 .…”
Section: Hrvmentioning
confidence: 95%
See 1 more Smart Citation
“…In both groups, LF (ms 2 ) values were considerably increased in magnitude but different from each other during CB, a condition known to augment cardiovagal control 21 . Nevertheless this finding does not reflect sympathetic dominance but rather an effect of low respiratory frequency (,0.2 Hz), which causes an overlap of the LF and HF components of CVV signals 22,26 .…”
Section: Hrvmentioning
confidence: 95%
“…LF (mmHg 2 ) was comparatively lower in PD during AS, this reduction in the so-called Mayer waves reflects an impairment in the vasosympathetic outflow 5,25 . Meanwhile, during SR, a similar though statistically not significant trend was noticed as shown in Figure. Vasosympathetic dysfunction in PD has been already reported 25,26 . The coincidence of LF (mmHg 2 ) comparatively decreased in PD and MSBP similar between groups after orthostatic challenge (i. e., AS) is consistent with a previously proposed hypothesis that initial alterations of vasosympathetic control may primarily affect BPV and only subsequently induce changes in MSBP values leading to orthostatic hypotension 25 .…”
Section: Bpvmentioning
confidence: 97%
“…Another autonomic disturbance is the postganglionic sympathetic denervation of the heart, which can be measured by iodine-123-metaiodobenzylguanidine SPECT. 5 Patients with idiopathic RBD may also show a significant reduction of heart rate variability. RBD is characterized by a loss of atony during REM sleep, 6 and patients with RBD physically and verbally act out their dreams.…”
mentioning
confidence: 99%
“…Recently, it has been reported that PD patients with TOH (PD+TOH) have a lower basal leg vascular resistance, which might suggest that sympathetic denervation is more pronounced in PD+TOH than in PD patients without TOH (PD-TOH) 8 . Yet, Oka et al documented that latent cardiac and vasomotor sympathetic dysfunction occurs in PD-TOH patients 9 . While the hemodynamic response to orthostatic stress has been already evaluated in PD-TOH 8 , IOH can be documented only by continuous beat-to-beat BP monitoring during AS 1 .…”
mentioning
confidence: 99%